The use of antibiotics in the early stage of acute exacerbation of chronic obstructive pulmonary disease in patients without obvious signs of infection: a multicenter, randomized, parallel-controlled study - Zhou, Ling; Deng, Yan; Liu, Kui; Liu, Huiguo; Liu, Wei (Frontiers in Pharmacology, 2024)
Introduction Chronic obstructive pulmonary disease (COPD) is a chronic respiratory disease with high prevalence and mortality. In some acute exacerbations of COPD (AECOPD) in patients with no obvious signs of infection, early antibiotic treatment seems to clinically improve the disease, but more studies are needed to determine the prognostic impact of antibiotic treatment in AECOPD patients with no obvious signs of infection. Purpose To clarify the impact of antibiotic treatment on the short-term and long-term prognoses of AECOPD patients without obvious signs of infection. Methods The impact of the two treatment methods on the prognosis of patients was compared at 30, 90, 180, and 360 days after discharge. A multicenter, randomized, parallel-controlled clinical trial was conducted in a department of respiratory and critical care medicine in Central China. All patients met the inclusion criteria for AECOPD, and the patients were randomly assigned to the antibiotic group or the nonantibiotic group at a 1:1 ratio. Patients in the antibiotic group were given moxifloxacin 400 mg/day intravenously for 7 days. Patients in the nonantibiotic group were intravenously injected with the same amount of normal saline as the amount of moxifloxacin given to those in the antibiotic group for 7 days. Results There were 406 patients in the antibiotic group and 410 patients in the nonantibiotic group. During the short-term and long-term follow-ups, the acute exacerbation frequency, intensive care unit (ICU) treatment rate, mortality, and mMRC and CAT scores were not significantly different between the two groups (p > 0.05). At the 180- and 360-day follow-ups, the forced expiratory volume in 1 s (FEV1%) and peak expiratory flow (PEF) were not significantly different between the two groups (p > 0.05). The 30-day readmission rate was significantly lower in the antibiotic group than in the nonantibiotic group (p < 0.05). The time from discharge to the first acute exacerbation was not significantly different between the two groups (p > 0.05). The length of the first hospital stay after discharge was significantly lower in the antibiotic group (5.84 days) than in the nonantibiotic group (6.75 days) (p < 0.05). At the 30-day follow-up, the acute exacerbation frequency, age, C-reactive protein (CRP) level, and sputum viscosity were significantly greater in the nonantibiotic group than in the antibiotic group (p < 0.05). In addition, according to the receiver operating characteristic (ROC) analysis, the frequency of acute exacerbations at the 30-day follow-up was significantly greater in COPD patients aged >62.5 years, with a CRP level >12.56 mg/L or with a sputum viscosity >III, in the nonantibiotic group than in those in the antibiotic group, suggesting that the short-term prognosis was poor. Conclusion Patients who are >62.5 years of age, have a CRP concentration >12.56 mg/L, or have a sputum viscosity >III without obvious signs of infection should be treated with antibiotics to improve their short-term prognosis. Clinical Trial Registration: (https://www.chictr.org.cn), (ChiCTR1800018921)